Two-color fluorescent cytosine extension assay for the determination of global DNA methylation - Gu Zhou; Craig Parfett; Cathy Cummings-Lorbetskie; Gong-Hua Xiao; Daniel Desaulniers (BioTechniques)
Here, we present a DNA restriction enzyme–based, fluorescent cytosine extension assay (CEA) to improve normalization and technical variation among sample-to-sample measurements. The assay includes end-labeling of parallel methylation-sensitive and methylation-insensitive DNA restriction enzyme digests along with co-purification and subsequent co-measurement of incorporated fluorescence. This non-radioactive, two-color fluorescent CEA (TCF-CEA) was shown to be a relatively rapid and accurate, with 3-fold greater precision than the one-color CEA. In addition, TCF-CEA provided an index of global DNA methylation that was sensitive to differences >5%. TCF-CEA results were highly correlated with LUminometric Methylation Assay (LUMA) results using human liver cell lines (HepG2, HepaRG, HC-04) as well as a human liver primary cell culture. Hypomethylation was observed in cells treated with the de-methylating agent 5-aza-2'-deoxycytidine. These results demonstrate that TCF-CEA provides a simple method for measuring relative degrees of global DNA methylation that could potentially be scaled up to higher-throughput formats.